Scaling Up DNA Origami Lattice Assembly. Issue 33 (4th May 2021) - Xin, Yang; Shen, Boxuan; Kostiainen, Mauri A.; Grundmeier, Guido; Castro, Mario; Linko, Veikko; Keller, Adrian
Abstract: The surface‐assisted hierarchical assembly of DNA origami nanostructures is a promising route to fabricate regular nanoscale lattices. In this work, the scalability of this approach is explored and the formation of a homogeneous polycrystalline DNA origami lattice at the mica‐electrolyte interface over a total surface area of 18.75 cm 2 is demonstrated. The topological analysis of more than 50 individual AFM images recorded at random locations over the sample surface showed only minuscule and random variations in the quality and order of the assembled lattice. The analysis of more than 450 fluorescence microscopy images of a quantum dot‐decorated DNA origami lattice further revealed a very homogeneous surface coverage over cm 2 areas with only minor boundary effects at the substrate edges. At total DNA costs of € 0.12 per cm 2, this large‐scale nanopatterning technique holds great promise for the fabrication of functional surfaces. Abstract : The surface‐assisted assembly of DNA origami lattices is a promising technique for fabricating functional surfaces. Here, the formation of a homogeneous DNA origami lattice on mica over a total surface area of 18.75 cm 2 is demonstrated. Atomic force and fluorescence microscopy mapping reveal the high uniformity and homogeneity of the lattice over almost the entire surface area. The total DNA costs amount to €0.12 per cm 2 .